Nitrogen uptake and transfer in broad bean and garlic strip intercropping systems - Qiu-xiang TANG; Haile Tewolde; Hong-bin LIU; Tian-zhi REN; Ping-an JIANG; Li-mei ZHAI; Bao-kun LEI; Tao LIN; En-ke LIU (Journal of Integrative Agriculture)
Utilization and transfer of nitrogen (N) in a strip intercropping system of garlic (Allium sativum L.) and broad bean (Vicia faba L.) have been investigated rarely. The objectives of this study were to quantify N uptake and utilization by intercropped broad bean and garlic and determine the magnitude of N transfer from broad bean to garlic. Field and pot trials were carried out in the Erhai Lake Basin in China using 15N tracer applied to the soil or injected into broad bean plants. Strip intercropping of garlic and broad bean increased N absorption (47.2%) compared with sole crop broad bean (31.9%) or sole crop garlic (40.7%) and reduced soil residual N. Nearly 15% of 15N injected into petioles of broad bean intercropped with garlic was recovered in garlic at harvest, suggesting that N could be transferred from broad bean to strip intercropped garlic. The findings provide a basis for evaluating legumes' role in optimizing N fertilization when intercropped with non-legumes.